2020
DOI: 10.3390/nu12092507
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Myristica fragrans Houtt. Extracts Against Obesity and Inflammation by Regulating Free Fatty Acids Metabolism in Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a disorder characterized by the excess accumulation of fat in the hepatocytes. It is commonly associated with severe obesity and inflammation. Free fatty acids (FFAs) are the key to regulate lipid metabolism and immune response in hepatocyte cells. This study examined the effects of AEN (alcohol extract of nutmeg, the seed of Myristica fragrans Houtt.) on the inhibition of lipid synthesis and inflammation in vitro and in vivo and on high-fat diet-induced obesity in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“… 32 In addition, treatment may downregulate the activity of numerous enzymes involved in TAG synthesis, such as acyl-CoA synthetases, acyltransferases glycerol-3-phosphate 4 (GPAT4), and diacylglycerol acyltransferase 2 (DGAT2), which allow for the expansion of preexisting lipid droplets. 29 Similar results were reported earlier, 33 , 34 where both have shown that downregulation of lipogenic-gene expression in the liver by Myristica fragrans Houtt. and Morus alba L. extracts inhibit the progression and development of NAFLD.…”
Section: Discussionsupporting
confidence: 87%
“… 32 In addition, treatment may downregulate the activity of numerous enzymes involved in TAG synthesis, such as acyl-CoA synthetases, acyltransferases glycerol-3-phosphate 4 (GPAT4), and diacylglycerol acyltransferase 2 (DGAT2), which allow for the expansion of preexisting lipid droplets. 29 Similar results were reported earlier, 33 , 34 where both have shown that downregulation of lipogenic-gene expression in the liver by Myristica fragrans Houtt. and Morus alba L. extracts inhibit the progression and development of NAFLD.…”
Section: Discussionsupporting
confidence: 87%
“…Models were fed with high-fat-diet. It was revealed from the study, alcohol extract of nutmeg significantly reduced the body weight and levels of inflammation, cholesterol and lipid accumulation, blood glucose which supports its use as an hepatoprotective agent [143]. Dkhil et al, also studied hepatoprotective activity of Myristica fragrans.…”
Section: Hepatoprotectivementioning
confidence: 87%
“…Administration of H 2 S reduced NEFA level in the liver of mice fed with HFD. It has been reported that pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) play important roles in the development of NAFLD ( Ji et al, 2018 ; Liu et al, 2020b ; Zhao et al, 2020 ). Our results indicated that H 2 S reduced the levels of TNF-α, IL-1β, and IL-6 in the liver of HFD-fed mice, suggesting that H 2 S may relieve NAFLD partly by decreasing inflammation in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…For ORO staining, the frozen tissues were cut into 10 μm thick sections, stained with ORO, and then counterstained with hematoxylin. The sections were observed using an Olympus BX51 microscope (Olympus, Tokyo, Japan) and analyzed by Image J software (National Institutes of Health, Bethesda, MD, United States), and the area of hepatic steatosis was determined using optical density values ( Zhao et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%